Entrepreneurship Orientation to Nurture the Halal Food Industry Future in Ethiopia - Gemechis Fikadu; Kenesa Kebede; Shashi Kant (Universitas Muhammadiyah Yogyakarta, 2023)
The concept of entrepreneurship is not unique in Islam, as observed from history, that the Prophet and His disciples engaged in it as a respectable profession. Islamic economic academics recently invented the term